Transferring the effect of learning from the skill of crushing to learning the aces in volleyball (Journal of the College of Basic Education, 2022)
Educational teaching should be taken into account to obtain a positive and appropriate transfer for the process of directing learning and developing educational skills.The research aims to identify the transfer of learning from the skill of multiplication to learning the game of volleyball; This is due to common factors between the two skills, the more there is an amount of common elements between the two skills, it becomes possible to transfer the effect of learning from one to the other, and in The skills of smashing and smashing There are common skills in terms of approaching, getting up and hitting the ball, directing it and then landing. The researchers assumed that the group that starts training with the smash hit skill outperforms the group that hopes to hit the smash, and the effect of learning is transmitted better in the group that trains the smasher Or not. The researchers used the experimental method, and the sample was chosen in a deliberate manner from the students of the second stage in the College of Physical Education and Sports Sciences - University of Anbar for the academic year (2019-2020), and its number was (70) seventy students divided into two groups, one of them is experimental and this group learns the crushing multiplication with its known steps And from Then he learned the skill of smashing, as for the second group, you start learning the skill of smashing, and then you learn the smash hit. The training is carried out according to the study schedule for six weeks and one training unit a week of (90) minutes with an additional unit. At the same time, the learning steps included approaching, getting up and hitting. The crushing and landing for both groups, the implementation of the field work after the explanation and clarification, the making of a kinetic model and the work with repetition for several times in the educational unit.Measuring the smashing skill and the smashing skill of the two groups using standardized skill tests for these two skills, and the researchers concluded that the group that trained first with smashing, the experimental group, had significant results and was better in learning smashing. Learn the skill of ace.